Pengaruh Persepsi Harga dan Kualitas Produk Terhadap Kepuasan Pelanggan Produk Skincare Skintific - Bagus Setiawan; Eka Dyah Setyaningsih; Vina Islamy (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the effect of price perception and product quality on customer satisfaction of Skintific skincare products. Price perception refers to the amount of money exchanged for a product or service, while product quality consists of various attributes that influence how well a product meets customer expectations. A higher product quality increases a company's chance of attracting customers. This research employed a quantitative method with a sample of 100 Skintific consumers. Data were collected through observation and questionnaires. The results showed that price perception has a positive and significant effect on customer satisfaction, with a t-value of 11.889 (t count > t table: 11.889 > 1.988). Likewise, product quality also has a significant effect on customer satisfaction, with a t-value of 17.025 (t count > t table: 17.025 > 1.988). Furthermore, the F-test result showed that the calculated F (220.109) is greater than the F-table value (3.09), indicating that price perception and product quality simultaneously have a significant influence on customer satisfaction. These findings highlight the importance for companies to pay attention to both price perception and product quality to increase consumer satisfaction with skincare products.